Tren Penelitian Nutrisi Anak Usia Dini: Analisis Bibliometrik Scopus - Aliyah, Rifatul; Hasibuan, Rachma; Rahmawati, Dina; Ratnaningsih, Hanifa Ayu; Nazar, Lailatun (AS-SABIQUN, 2025)
This study is motivated by the limited availability of comprehensive bibliometric analyses on research trends in early childhood nutrition, despite the significant impact of child nutrition issues on growth, optimal development, and global nutrition policy directions. The aim of this research is to analyze publication trends, identify leading contributors, determine prominent journals, uncover dominant themes, and provide implications for the development of early childhood nutrition research based on data from the Scopus database. A quantitative descriptive method with a bibliometric analysis design was employed by selecting scientific documents containing the keywords “nutrition” and “childhood,” written in English, indexed in Scopus, and published between 2020 and 2024 with complete metadata based on inclusion criteria. Data were analyzed using VOSviewer software to map publication trends, thematic clusters, and collaboration patterns among researchers and institutions. The results show fluctuations in publication volume, peaking in 2023, and the identification of eight main thematic clusters, covering key topics such as obesity, malnutrition, nutrition literacy, and health education interventions. These findings reinforce the relevance of child development theory and health literacy, and highlight the importance of mapping the scientific landscape to support more targeted and interdisciplinary nutrition intervention strategies. The implications of this study include theoretical contributions in the form of a systematic understanding of the evolution of child nutrition research, and practical recommendations for researchers, policymakers, and practitioners to design effective evidence-based interventions. The study also opens further exploration opportunities into the causes of publication fluctuations, database expansion, and qualitative content analysis of the research.